2015
DOI: 10.1002/tox.22225
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry (Vaccinium ashei Reade) extract ameliorates ovarian damage induced by subchronic cadmium exposure in mice: Potential δ‐ALA‐D involvement

Abstract: Females are born with a finite number of oocyte-containing follicles and ovary damage results in reduced fertility. Cadmium accumulates in the reproductive system, damaging it, and the cigarette smoke is a potential exposure route. Natural therapies are relevant to health benefits and disease prevention. This study verified the effect of cadmium exposure on the ovaries of mice and the blueberry extract as a potential therapy. Blueberry therapy was effective in restoring reactive species levels and δ-aminolevul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Previous research showed that quercetin treatment can prevent chronic Cd-induced oxidative stress and renal tubular damage. In addition, quercetin has shown its efficient action in the reproductive system of animals affected by the heavy metal Cd, restoring the activity of germ cells and improving the survival of follicles damaged by Cd [ 127 ]. The above studies have verified the inhibitory effects of quercetin on Cd-induced oxidative stress and other toxic functions, and further studies have shown that the combined treatment with α-tocopherol (AT) and quercetin provided more significant protection against Cd-induced oxidative stress and lipid metabolism compared with quercetin alone, thereby reducing Cd-induced cardiovascular disease [ 128 ].…”
Section: Preventing Poisoning As An Application Of Quercetinmentioning
confidence: 99%
“…Previous research showed that quercetin treatment can prevent chronic Cd-induced oxidative stress and renal tubular damage. In addition, quercetin has shown its efficient action in the reproductive system of animals affected by the heavy metal Cd, restoring the activity of germ cells and improving the survival of follicles damaged by Cd [ 127 ]. The above studies have verified the inhibitory effects of quercetin on Cd-induced oxidative stress and other toxic functions, and further studies have shown that the combined treatment with α-tocopherol (AT) and quercetin provided more significant protection against Cd-induced oxidative stress and lipid metabolism compared with quercetin alone, thereby reducing Cd-induced cardiovascular disease [ 128 ].…”
Section: Preventing Poisoning As An Application Of Quercetinmentioning
confidence: 99%
“…QUR as a natural antioxidant was used against the gonadotoxic effects of cadmium on the ovaries of rats and mice through scavenging free radicals and improving the activities of other antioxidants such as catalase, SOD, and GPx. Therefore, it improved the ovaries' health by increasing the secretion of estradiol, FSH, and LH (Izaguirry et al, 2017; Nna, Usman, Ofutet, & Owu, 2017). Since QUR is one of the main components of hydrolyzed and crude extracts of chia seeds (Reyes‐Caudillo, Tecante, & Valdivia‐López, 2008), Tarko et al used xylene, as an environmental contaminant, and different doses of chia seed extract (1, 10 and 100 ng ml −1 ) separately or together to investigate their effects on bovine ovarian cells activity (Tarko et al, 2017).…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…QUR as a natural antioxidant was used against the gonadotoxic effects of cadmium on the ovaries of rats and mice through scavenging free radicals and improving the activities of other antioxidants such as catalase, SOD, and GPx. Therefore, it improved the ovaries' health by increasing the secretion of estradiol, FSH, and LH (Izaguirry et al, 2017;Nna, Usman, Ofutet, & Owu, 2017). Since (Wang et al, 2018).…”
Section: Qur and Ovarymentioning
confidence: 99%
“…It is very important to notice that polyphenols are effective in offering protection from Cd toxicity to other organs and tissues, including the kidneys and skeleton, indicating the beneficial influence of these compounds on the whole organism (Aly et al, ; Baiomy & Mansour, ; Brzóska et al, ; Brzóska, Gałażyn‐Sidorczuk, et al, ; Brzóska, Rogalska, et al, ; Brzóska, Rogalska, et al, ; Farag et al, ; Izaguirry et al, ; Kopeć et al, ; Wani et al, ). Moreover, polyphenolic compounds are known to protect the liver from the hepatotoxic action of other xenobiotics such as diethylnitrosamine, Pb and As (Bingül et al, ; Choudhury et al, ; Kopeć et al, ; Winiarska‐Mieczan, ).…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…Available data in the literature indicate that, due to strong antioxidative properties, blueberry offers protection against oxidative stress‐related diseases (cancer, diabetes and heart disease) and inflammation, as well as improving eye condition (Routray & Orsat, ). It has been shown that blueberry extract ameliorated ovarian damage in mice subchronically exposed to Cd (Izaguirry et al, ). There is also evidence suggesting the hepatoprotective impact of blueberry under intoxication with this metal (Gong et al, ).…”
Section: Polyphenol‐rich Products In Protection and Treatment Of Cd‐imentioning
confidence: 99%